Trailer backing-up assistant using ultrasound sensors based control units to safely back-up the car with trailer - Josef, Vejlupek (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
This paper deals with the idea of upgrading the current car parking assistants based on ultrasonic sensors to enable them to assist with backing-up with trailer attached to the car. Basic ideas, models and algorithms are presented in this paper. Although commercial solution of the trailer backing-up assistant is already on the market, this approach is unique in extending the use of ultrasonic sensors. Therefore significance of this paper is purely academic in its main goal, however the presented ideas may be still usefull.